2002
DOI: 10.1080/10715760290021306
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Redox Activity of Coenzyme Q 10 : Effect of CoQ 10 Supplementation on Human Skeletal Muscle

Abstract: In this paper, we report results obtained from a continuing clinical trial on the effect of coenzyme Q10 (CoQ10) administration on human vastus lateralis (quadriceps) skeletal muscle. Muscle samples, obtained from aged individuals receiving placebo or CoQ10 supplementation (300mg per day for four weeks prior to hip replacement surgery) were analysed for changes in gene and protein expression and in muscle fibre type composition. Microarray analysis (Affymetrix U95A human oligonucleotide array) using a change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 37 publications
1
49
0
1
Order By: Relevance
“…Blood CoQ10 levels of 2.4 lg/ml were demonstrated as having the highest benefit in congestive heart failure, while levels of at least 3.4 lg/ml were needed before therapeutic effects were seen from dietary supplementation in patients with congestive heart failure (Linnane et al, 2002). However, in neurodegenerative disease conditions the required plasma threshold levels appear to be much higher to produce a clinical response.…”
Section: Discussionmentioning
confidence: 87%
“…Blood CoQ10 levels of 2.4 lg/ml were demonstrated as having the highest benefit in congestive heart failure, while levels of at least 3.4 lg/ml were needed before therapeutic effects were seen from dietary supplementation in patients with congestive heart failure (Linnane et al, 2002). However, in neurodegenerative disease conditions the required plasma threshold levels appear to be much higher to produce a clinical response.…”
Section: Discussionmentioning
confidence: 87%
“…The molecular mechanisms by which CoQ 10 mediates these beneficial effects are uncertain. We (25) and others (26,27) obtained evidence that CoQ 10 influences the expression of hundreds of genes involved in different cellular pathways. To decipher the functional and regulatory connections of these genes we employed bioinformatic techniques to access the actions of CoQ 10 in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Age related decline in bioenergy capacity below a crucial threshold will obviously contribute to cellular malfunction. The development of mitochondrial tissue bioenergy mosaics with age, exemplified by null, low and normal cytochrome oxidase cell content has been stringently correlated at the single cell level by our laboratory, with mtDNA deletions and the individual cell content of full-length functional mtDNA (Nagley et al 1993;Kovalenko et al 1998;Kopsidas et al 2000Kopsidas et al , 2002Linnane et al 2002a). The mtDNA deletion changes reported by us mainly arise by replication error due to the asymmetrical nature of the heavy and light strand synthesis and the very large number of base pair repeats which mismatch during replication and result in mtDNA deletions.…”
Section: Mitochondrial Dnamentioning
confidence: 95%
“…We have earlier reported that coenzyme Q 10 functions in the process of gene regulation (Linnane et al 2002a;Linnane 2002b). This conclusion arose from administering coenzyme Q 10 in a placebo controlled trial to patients for a period of 4 weeks prior to undergoing hip replacement surgery.…”
Section: Superoxide Anion and Hydrogen Peroxide Formationmentioning
confidence: 97%